2006
DOI: 10.1097/00000542-200610000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Pain after Cardiac Surgery

Abstract: Although common, the incidence of persistent pain after sternotomy was lower than previously reported. Also, reassuringly, 1 year after surgery this pain was mostly mild in nature both at rest and on movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(92 citation statements)
references
References 15 publications
3
76
0
1
Order By: Relevance
“…In our analysis, pneumonia was a primary driver of HAI rates. Interventions aimed at preventing pneumonia and other pulmonary complications may include: encouraging pre-operative respiratory muscle training 20 and smoking cessation, 21, 22 improving post-operative analgesia, 23, 24 encouraging post-operative incentive spirometry use, 25 and selective use of post-operative continuous positive airway pressure. 26, 27 Future research is warranted to assess the effectiveness of these interventions in reducing the pneumonia-related HAI rates in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, pneumonia was a primary driver of HAI rates. Interventions aimed at preventing pneumonia and other pulmonary complications may include: encouraging pre-operative respiratory muscle training 20 and smoking cessation, 21, 22 improving post-operative analgesia, 23, 24 encouraging post-operative incentive spirometry use, 25 and selective use of post-operative continuous positive airway pressure. 26, 27 Future research is warranted to assess the effectiveness of these interventions in reducing the pneumonia-related HAI rates in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher incidence of chronic (21% -55%) [1] pain in cardiac surgery patients due to various reasons. Pain after cardiac surgery is different from other surgeries mainly because of various sites of origin of pain and several aggravating factors.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent pain since the operation is commonly described as chest pain with movement4 and is often musculoskeletal in origin.…”
Section: What To Cover On Initial Assessment?mentioning
confidence: 99%
“…Recurrent or chronic chest pain after CABG can be extremely worrying for the patient and affect their quality of life 3. In a prospective cohort study (183 patients), a third of patients reported chronic chest pain on movement and 17% reported chest pain at rest at one year after CABG 4. This presents a diagnostic challenge in primary care and requires prompt investigation 5…”
mentioning
confidence: 99%